ANALISIS PRODUK LAYANAN RS APUNG NUSA WALUYA 2 MENURUT CARA BAURAN PEMASARAN - Lubis, Ivan Reynaldo; Melissa, Hilda; Suwandi, Indah Pratiwi; Manik, Irfan Rohot Uli; Sulistiadi, Wahyu (UI Scholars Hub, 2024)
Hospitals as health service institutions are essential for society. However, in Indonesia, hospitals are not always available in areas far from regional or city government centers. Floating hospitals are an alternative that plays a significant role in island countries such as Indonesia. Even though the number of floating hospitals is very limited, marketing strategies through a marketing mix are still needed for their development, whether assessed from a business or non-business perspective. This study used a descriptive-analytical approach by collecting data from observations and collecting literature as the discussion material. As a result of simple observations and analysis, this study found that the Nusa Waluya 2 Floating Hospital had implemented marketing mix principles by various existing theories. However, the Nusa Waluya 2 Floating Hospital still needs to redesign and plan a more mature marketing strategy. The strategy focuses explicitly on its healthcare product mix. By applying the principles of a better marketing mix, it is hoped that the vision and mission of Nusa Waluya 2 Floating Hospital can be realized.